SISTEM INFORMASI PEMESANAN MOBIL BOX BERBASIS WEB PADA CV. KARUNIA TRANS CIKARANG - Hutagalung, Eka Karlina; Putra, Mardi Yudhi (JURNAL MAHASISWA BINA INSANI; Vol 8 No 1 (2023): Jurnal Mahasiswa Bina Insani (Agustus 2023), 2023)
The rapid development of technology has made the process of ordering box cars easier. The box car business currently uses technology to manage information and provide efficient and effective services for customers. This facilitates the box car business, and minimizes the risk of the box car business. Therefore, the company does not have a detailed or structured SOP (standard operating procedure), then does not have a system that can cover current orders, but currently the order is completely online but the order is still by telephone and still uses handwriting for the recording process. The Information System is made web-based using the Extreme Programming (XP) development method. In the system design stage, modeling is done in the form of UML diagrams based on functional requirements, then implemented through program code using Visual Studio Code, PHP and MySql programming languages. The results achieved from this research is a web-based box car ordering information system, with this ordering information system it can increase box car orders even more. The box car ordering information system is very helpful in transacting box car orders and makes it easier for Finance managers to view box car orders reports.